1988
DOI: 10.1002/mrm.1910070203
|View full text |Cite
|
Sign up to set email alerts
|

Acute volume loading studied in cat myocardium with 31P Nuclear magnetic resonance

Abstract: To study the effects of acute volume loading on myocardial metabolic and mechanical function, seven cats were volume loaded via anastomosis of the abdominal aorta to the vena cava (AV shunt). Metabolic effects were evaluated with 31P nuclear magnetic resonance (NMR). Mechanical function was evaluated with heart rate X systolic blood pressure product (HR X SBP). Shunts were opened for 1-2 h during which time phosphocreatine (PCr), adenosine triphosphate (ATP), inorganic phosphate (Pi), and HR X SBP were monitor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

1989
1989
2004
2004

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…NMR spectroscopy [18] in an acute, close-chested procine model with a surface coil directly sutured to the anterior epicardial surface of the left ventricle has demonstrated that creatine kinase flux and concentrations of PCr and ATP were independent of work load over a 2.5-fold range of cardiac rate-pressure products in response to the infusion of norepinephrine (2-5 micrograms/minute). Cat hearts appear more sensitive to changes in work than canine hearts [20]. Cat hearts appear more sensitive to changes in work than canine hearts [20].…”
Section: Previous Studies: Large Animal Modelsmentioning
confidence: 89%
“…NMR spectroscopy [18] in an acute, close-chested procine model with a surface coil directly sutured to the anterior epicardial surface of the left ventricle has demonstrated that creatine kinase flux and concentrations of PCr and ATP were independent of work load over a 2.5-fold range of cardiac rate-pressure products in response to the infusion of norepinephrine (2-5 micrograms/minute). Cat hearts appear more sensitive to changes in work than canine hearts [20]. Cat hearts appear more sensitive to changes in work than canine hearts [20].…”
Section: Previous Studies: Large Animal Modelsmentioning
confidence: 89%
“…Cardiac and respiratory gating were used to trigger both the satu ration and acquisition radio frequencies (RF). A rep resentative set o f 3IP spectra obtained during satura tion o f yP-ATP in a volume o f myocardial tissue (ap proximately 2 cm2) [1] is shown in figure 2. Progres sive saturation o f the yP-ATP was associated with a progressive decrease in PCr peak area.…”
Section: J P N M R Measurementsmentioning
confidence: 99%
“…Both the light guide and surface coil were positioned so that they did not overlie visible surface coronary ves sels. A multibundle fiberoptic light guide, 4 mm in diameter, was placed into the light guide holder and used in conjunction with a custom-built fluorometer to measure N A D H fluorescence [1],…”
Section: Animal Modelmentioning
confidence: 99%
“…Using a program which models the sensitivity pro file of a surface coil [22], we determined that practi cally all of the 11P NMR signal was obtained from left ventricular myocardium. The average wall thickness of the dog left ventricle at end systole was 1-1.2 cm (measured with piezoelectric crystals at the end of each experiment).…”
Section: Validation O F Nmr Signal Localizationmentioning
confidence: 99%
“…To do this, the respirator was instrumented with a switch which was turned on at end expiration. This signal plus a signal from a pressure transducer (which monitored the dog's systemic arterial pressure) were fed into a triggering box (built in our laboratory) [22]. The first positive upstroke from the pressure transducer during the end expiration period was used to trigger the radiofrequency stimulation.…”
Section: Nmr Experimentsmentioning
confidence: 99%